THE RELATIONSHIP BETWEEN DIET AND LONGEVITY: UNDERSTANDING HOW NUTRIENTS INFLUENCE HEALTH AND WELL-BEING - Pereira, Karliano Antônio Rôla (LUMEN ET VIRTUS, 2023)
Diet plays a pivotal role in shaping human health and longevity. A growing body of scientific literature has highlighted the importance of nutrient quality, caloric intake, and dietary patterns in preventing chronic diseases and promoting a longer, healthier life. This article explores how various nutrients—including macronutrients, micronutrients, and bioactive compounds—interact with physiological processes that influence aging, inflammation, and metabolic function. It also examines the emerging role of gut microbiota, meal timing strategies, and personalized nutrition in extending healthspan. Evidence supports the adoption of diets rich in whole plant foods, healthy fats, and moderate caloric intake as effective strategies for promoting well-being and longevity. Understanding these complex relationships is essential for developing public health policies and individual interventions aimed at enhancing life expectancy and quality of life.